Gambaran Student Engagement dalam Pembelajaran di Era New Normal - Nolla Gladisia; Nadhirotul Laily; Noer Suci Endah Puspitaningrum (Ilmu Psikologi Universitas Yudharta Pasuruan, 2022)
This study is to find out the description of Student Engagement in learning in the New Normal Era in grade VII students of SMP "X" which includes aspects of behavioral involvement, emotional involvement, and cognitive involvement, factors that influence Student Engagement and the resulting impact of Student Engagement. This research approach is qualitative with phenomenological method. The subjects in the study were five seventh grade students at "X" Junior High School who were facing learning in the New Normal Era. Interview and observation data collection techniques. The data analysis technique uses the Miles and Hubberman model. The credibility technique used is triangulation. The results of this study explain that, based on the background of the subject, the subject experiences different student engagement. As for student engagement, such as: (1) positive engagement, non-engagement, and negative engagement, (2) Factors affecting Student Engagement consist of internal and external factors, and (3) Impact of Student Engagement. Student engagement shows learning methods that are suitable for students.